Screening design and construction technologies of skyscrapers. Issue 3 (1st July 2014) - AboMoslim, Saad; Russell, Alan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to study screening design and construction technologies of skyscrapers. Skyscraper projects provide an illustration of important driving factors (e.g. economies of scale and international expertise) when utilising a wide range of solutions, including innovative ones, in the design and construction of building systems and subsystems. The need exists for a methodology for the speedy screening and comprehensive evaluation of candidate solutions covering the complete spectrum of systems that comprise a building project and that have an impact on life cycle performance. Presented in this paper is a three-step evaluation framework directed at meeting this need, along with application of the first step to three case studies performance. Design/methodology/approach – Research objectives were achieved by an extensive literature review of the current state-of-the-art evaluation tools and criteria; formulation of a three-step evaluation process for screening and ranking candidates; identification and structuring of comprehensive checklists of evaluation criteria; application of the first step of the evaluation framework to three case studies to gauge completeness and ease of use; and assessment of the framework by experienced practitioners. Findings – The framework proposed provides a structured and transparent approach to assessing design/construction choices. It makes explicit the spectrum of criteria to be considered when assessing their feasibility. Feedback from industry professionals indicates that the framework is reflective of industry needs. Originality/value – The originality and value of the approach lies in the comprehensiveness of the criteria considered, their relevance to signature building projects that draw on international expertise and technologies and their relevance to all phases of the project life cycle.